Compactons and topological solitons of the Drinfel'd-Sokolov system - İnç, Mustafa; Fendoglu, Eda; Triki, Houria; Biswas, Anjan (Inst Mathematics & Informatics, 2014)
This paper presents the Drinfel'd-Sokolov system (shortly D(m, n)) in a detailed fashion. The Jacobi's elliptic function method is employed to extract the cnoidal and snoidal wave solutions. The compacton and solitary pattern solutions are also retrieved. The ansatz method is applied to extract the topological 1-soliton solutions of the D (m, n) with generalized evolution. There are a couple of constraint conditions that will fall out in order to exist the topological soliton solutions.
Keywords: Drinfe'd-Sokolov system; Jacobi elliptic function; compacton and solitary pattern solutions; topological soliton